SCREENING BAKTERI AMILOLITIK DAN SELULOLITIK DARI LIMBAH SAGU (Screening of Amylolytic and Cellulolytic Bacteria From Sago waste) - Yanti, Nur Arfa (REZ PUBLICA, 2015)
ABSTRACTScreening of indigenous bacteria from sago waste based on amylolytic and cellulolytic activitywas done to obtain bacterial isolate having double activity, i.e. could to hydrolize of starch(amylolytic) and cellulose (cellulolytic). Screening amylolytic and cellulolytic bacteria wasdone based on amylolytic and cellulolytic activity on agar media. Determination of amylolyticactivity on starch agar media was based on the presence of clear zone around the bacterialcolony upon flooding with lugol’s iodine solution. Cellulolytic activity was determine based onthe presence of clear zone around the bacterial colony on Carboxy methyl cellulose (CMC)agar upon flooding with congo red solution. Presence of a clear zone around the colonyindicated starch and cellulose hydrolysis. The diameters of clear zone produced on CMC andstarch agar were measured and used as an indication of the amylolytic and cellulolyticactivities of the bacteria. The results of the screening based on amylolytic and cellulolyticactivity showed that a number of 21 bacterial isolates that having both activities. LCA2 was thebacterial isolate with the highest amylolytic and cellulolytic activity as revealed by the size ofclearing zone on both types of agar plates. The diameters of clear zone on starch and CMCagar were 4,98 and 3,65 cm2, respectively. Therefore, LCA2 isolate was bacterial isolate thatpotent for biconvertion sago hampas into value-added products